2022
DOI: 10.1177/25151355221115011
|View full text |Cite
|
Sign up to set email alerts
|

T cells in SARS-CoV-2 infection and vaccination

Abstract: While antibodies garner the lion’s share of attention in SARS-CoV-2 immunity, cellular immunity (T cells) may be equally, if not more important, in controlling infection. Both CD8+ and CD4+ T cells are elicited earlier and are associated with milder disease, than antibodies, and T-cell activation appears to be necessary for control of infection. Variants of concern (VOCs) such as Omicron have escaped the neutralizing antibody responses after two mRNA vaccine doses, but T-cell immunity is largely intact. The br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Studies published between 2021 and 2022 showed high SARS-CoV-2-specific T-cell activation following severe disease 21 and impaired protection from infection in rhesus macaques ( Macaca mulatta ) following CD8 T-cell depletion, 22 suggesting that cellular immunity can contribute to protection against SARS-CoV-2. It was proposed that memory T cells might protect populations from severe infections, 23 , 24 perhaps when antibody titres are waning. In our study, only five participants with confirmed SARS-CoV-2 infection had severe disease and T-cell activation was measured in only one of these individuals, precluding analysis of a correlation between T-cell activation and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published between 2021 and 2022 showed high SARS-CoV-2-specific T-cell activation following severe disease 21 and impaired protection from infection in rhesus macaques ( Macaca mulatta ) following CD8 T-cell depletion, 22 suggesting that cellular immunity can contribute to protection against SARS-CoV-2. It was proposed that memory T cells might protect populations from severe infections, 23 , 24 perhaps when antibody titres are waning. In our study, only five participants with confirmed SARS-CoV-2 infection had severe disease and T-cell activation was measured in only one of these individuals, precluding analysis of a correlation between T-cell activation and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells enhance the antibody and cytotoxic T lymphocyte responses. CD8 + T cells recognize virus-infected cells and eliminate them to limit viral spread ( Young, 2022 ). To precisely characterize the SARS-CoV-2 VLP activity on DC and T cell interactions, the syngeneic MLR assay was performed, which revealed that SARS-CoV-2 VLP treatment enhanced CD4 + and CD8 + T cell proliferation ( Figures 6A, B ).…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19, high T cell activity response is associated with milder disease, whereas a poor T cell response is associated with severe disease ( Young, 2022 ). In the present study, interestingly, the proliferation of both CD4 + and CD8 + T cells was negatively correlated with the concentration of VLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only assessed antibody titers and cross-reactivity after infection and vaccination. Protection against reinfection and, importantly, against serious disease will also depend T-cell responses, 35 which we did not assess in our cohort.…”
Section: Discussionmentioning
confidence: 99%